2018
DOI: 10.1002/pc.24830
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale enhancement behavior of nano‐silica modified CF/PEEK composites prepared by wet powder impregnation

Abstract: The mechanical performance of modified multiscale carbon fiber (CF) reinforced poly(ether-ether-ketone) (PEEK) composites is improved through wet powder impregnation. The complex PEEK suspension is prepared by mixing nano-silica and PEEK powders in water homogeneously. The CFs are pulled through the complex PEEK suspension, and the modified multiscale PEEK prepregs and composites are prepared by a series of drying and consolidation process. The increasing energy storage, decreasing tan d max and the area under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Su et al’ method need second fabrication for prepreg to introduce nanoparticles, which also expands the work. To meet the continuous manufacturing requirement of commercial application, aqueous suspension prepregging, an efficient and environmental friendly way for CFRTP manufacture, is employed to prepare nanoparticles‐modified CFRTP by dispersing the nanoparticles in the suspension during processing, which was confirmed feasible by our previous work …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Su et al’ method need second fabrication for prepreg to introduce nanoparticles, which also expands the work. To meet the continuous manufacturing requirement of commercial application, aqueous suspension prepregging, an efficient and environmental friendly way for CFRTP manufacture, is employed to prepare nanoparticles‐modified CFRTP by dispersing the nanoparticles in the suspension during processing, which was confirmed feasible by our previous work …”
Section: Introductionmentioning
confidence: 77%
“…However, compared to pristine specimen, the image of the specimen modified with 1 wt% MWNTs revealed fewer and smaller cracks, demonstrating the strong interlaminar interactions. Load–Displacement curve showed the initiation of the cracks in 1 wt% MWNTs load specimen occurred on larger strain indicating the presence of MWNTS in the PPS matrix increased the resistance to cracks initiation. However, excessive addition of the MWNTs caused undesirable results.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al added a small amount of surfactant (Triton) to deionized water to achieve the dispersion of PEEK in water. The suspension can remain stable for a certain period of time 27 . However, it was found that settlement stratification appeared soon after suspension was standing.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that by selecting appropriate surfactant formulations and processes, the suspension stability can be improved. 28 Surfactants can be divided into non-ionic surfactants, cationic surfactants and anionic surfactants. Different surfactants have different mechanisms to stabilize the suspension.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the ILSS, flexural strength and modulus of the resulting CF/PEEK composites increased by 70%, 37%, and 48%, respectively. Chen et al 17 evenly mixed nano‐SiO2 and PEEK powder in water to prepare a PEEK composite suspension. A modified multi‐scale PEEK prepreg and its composites were then prepared via a series of curing processes.…”
Section: Introductionmentioning
confidence: 99%